Well-being across America - Andrew J. Oswald; Stephen Wu (Institute for the Study of Labor (IZA), 2009)
This paper uses new Behavioral Risk Factor Surveillance System data to provide the first estimates of well-being across the states of America. From this sample of 1.3 million US citizens, we analyze measures of life satisfaction and mental health. Adjusting for people's characteristics, states such as Louisiana and DC have high psychological well-being levels while California and West Virginia have low well-being; there is no correlation between states' well-being and their GDP per capita. Correcting for people's incomes, satisfaction with life is lowest in the rich states. We discuss implications for the arbitrage theory that regions provide equal utility and compensating differentials.
Keywords: D1; I3; 330; Compensating differentials; BRFSS; happiness; geography; GHQ; Easterlin Paradox; mental health; depression; life course; Lebenszufriedenheit; Messung; Psychische Störung; Regionale Einkommensverteilung; USA